The risk of community-acquired pneumonia among 9803 patients with coeliac disease compared to the general population: a cohort study - Zingone, Fabiana; Abdul Sultan, Alyshah; Crooks, Colin J.; Tata, Laila J.; Ciacci, Carolina; West, Joe (Wiley, 2016)
Background: Patients with coeliac disease are considered as individuals for whom pneumococcal vaccination is advocated.